2014
DOI: 10.1007/s10147-014-0759-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of receptor discordance between primary and recurrent breast cancer

Abstract: Discordance in receptor status between primary and recurrent breast cancers were seen in 10-30 %. A gain in HR status was significantly associated with better prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…The reason behind the decreased ER expression of BC#1 was surmised as follows. It has been reported that the hormone receptor discordance between primary and recurrent BC has occurred at the frequency of 10–40%, because of the change in tumor characteristics after treatment . In addition, it is known that long‐term estrogen deprivation in culture causes the instability of ER expression in vitro .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason behind the decreased ER expression of BC#1 was surmised as follows. It has been reported that the hormone receptor discordance between primary and recurrent BC has occurred at the frequency of 10–40%, because of the change in tumor characteristics after treatment . In addition, it is known that long‐term estrogen deprivation in culture causes the instability of ER expression in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the hormone receptor discordance between primary and recurrent BC has occurred at the frequency of 10-40%, because of the change in tumor characteristics after treatment. (38) In addition, it is known that longterm estrogen deprivation in culture causes the instability of ER expression in vitro. (39) These factors might cause the discrepancy of the ER expression in BC#1 cells isolated from the pleural effusion.…”
Section: Resultsmentioning
confidence: 99%
“…According to studies on ER, PgR, and HER2 discordance between the primary focus and metastatic foci, the discordance rate has been reported as 10–18% for ER, 25–40% for PgR [10, 13, 14], and 3–24% for HER2 [10, 13, 14, 15]. In 14–64% of these cases, the treatment strategy was modified based on the discordance [13, 14, 15].…”
Section: Discussionmentioning
confidence: 99%
“…In 14–64% of these cases, the treatment strategy was modified based on the discordance [13, 14, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…Tissue confirmation led to changes in treatment for 14.2% of patients (37). When we evaluated 55 patients who had undergone biopsies or resections of recurrent lesions, discordance rates for ER, PgR and HER2 status were 16.4, 30.9 and 10.2%, respectively (38). Some retrospective studies report an association between changes in receptor status and poor prognosis (39,40).…”
Section: Discordance In Biomarker Status Between Primary and Recurrenmentioning
confidence: 99%